A novel Cl- modification approach to develop highly efficient photocatalytic oxygen evolution over BiVO4 with AQE of 34.6%. (March 2021) - Zhang, Qiqi; Liu, Min; Zhou, Wei; Zhang, Yajun; Hao, Weichang; Kuang, Yongbo; Liu, Huimin; Wang, Defa; Liu, Lequan; Ye, Jinhua
Abstract: Water oxidation with multielectron transfer is regarded as the crucial step in photocatalytic water splitting. However, a facile but efficient method to promote its slow kinetics is still highly demanding. This work demonstrates that Cl - surface modification drastically enhances photocatalytic water oxidation over BiVO4 as well as WO3 . The optimal modified BiVO4 achieves a photocatalytic activity of 4.2 orders enhancement relative to the pristine BiVO4, giving up to an excellent apparent quantum efficiency of 34.6% at 420 nm. Cl - -modified 30-facet BiVO4 with 2.6 times enhancement confirms that the surface reaction involved with photogenerated holes can be dramatically accelerated by Cl - modification in addition to enhanced charge carrier separation. Our results highlight the impact of Cl - modification on the reaction kinetics and pathway during the photocatalytic water oxidation process, which has been mostly overlooked. Systematic studies (DFT simulations, kinetic experiments) reveal that Cl - modification remarkably reduces the photocatalytic water oxidation energy barrier and alters reaction pathway, which is also manifested in facilitated H2 O molecule activation in synchronous illumination XPS (SI-XPS) study. The EXAFS and angle-resolved XPS (AR-XPS) results show that Cl bonds to Bi and mainly concentrates on the surface of modified BiVO4 . Our findings provide an effective and facile approach to exploring efficient O2 evolution semiconductors for photocatalytic water splitting. Graphical Abstract: ga1 Highlights: Facile Cl - modification remarkably enhances photocatalytic water oxidation on BiVO4 . The optimal modified BiVO4 possesses an AQE of 34.6% at 420 nm. Surface photocatalytic water oxidation dramatically accelerated by Cl - modification. DFT calculation and kinetic studies demonstrates reduced activation energy barrier. EXAFS and AR-XPS clarify the coordination and spatial distribution of Cl.